Letters of the Sultans of Banten in the National Archives of the Republic of Indonesia - Titik Pudjiastuti, (Universiti Kebangsaan Malaysia, 2005)
In this article, I will discuss letters of the Sultans of Banten. I start with their physical aspect, followed by the composition of the letters, the scripts, and the language. The appendix contains a photocopy of both of letters, together with a transliteration of the texts